Pengaruh Aset Pajak Tangguhan dan Ukuran Perusahaan Terhadap Manajemen Laba (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Mala, Yohanes Jeiwu; Masyhad; Inayah, Nur Lailiyatul; Devi, Fitriyah Kusuma; Al Hamzah, Muhammad Habibie (Asosiasi Dosen Akuntansi Indonesia, 2025)
The purpose of this research is to examine the size of deferred tax assets and company size to predict earnings management carried out by company managers. With purposive sampling, 102 manufacturing companies listed on the Indonesia Stock Exchange were collected in 2018-2020. The data was then processed using multiple regression analysis. The research results prove that deferred tax assets and company size influence predicting earnings management carried out by company management. The research results also show that Deferred Tax Assets and Company Size simultaneously and partially influence earnings management. This research answers the hypothesis that deferred tax assets and company size influence predicting earnings management.